Effect and Safety of Therapeutic Regimens for Patients With Germline BRCA Mutation-Associated Breast Cancer: A Network Meta-Analysis - Jiang, Ying; Meng, Xiang-Yu; Deng, Ning-Ning; Meng, Chen; Li, Lu-Hui; He, Zi-Kang; Wang, Xing-Yun; Song, Zhe-Yao; Cui, Rong-Jun (Frontiers in Oncology, 2021)
Purpose Breast cancer type 1 susceptibility (BRCA) mutations not only increase breast cancer (BC) risk but also result in poor survival and prognosis for BC patients. This study will analyze the effect and safety of therapeutic regimens for the treatment of BC patients with germline BRCA (gBRCA) mutations by network meta-analysis. Methods Public databases were searched from inception to 29 April 2021. Frequentist network meta-analysis was conducted to analyze the benefit of chemotherapy and targeted drug-related strategies. Results Seventeen articles were included in the analysis. For progression-free survival (PFS), olaparib (hazard ratio (HR): 0.58; 95% confidence interval (CI): 0.43 – 0.79), platinum (HR: 0.45; 95% CI: 0.22 – 0.89), and talazoparib (HR: 0.54; 95% CI: 0.41 – 0.71) were significantly better than platinum-free chemotherapy (Chemo). The results based on indirect comparisons showed that veliparib (Vel) + platinum + Chemo was also significantly better than Chemo (HR: 0.37; 95% CI: 0.20 – 0.69). For overall survival (OS), olaparib was significantly better than Chemo only in the population who did not receive prior chemotherapy. For pathologic complete response (pCR), bevacizumab+Chemo had a significant advantage over platinum agents (OR: 3.64; 95% CI: 1.07 - 12.39). Olaparib and talazoparib both showed significantly higher objective response rates (ORRs) than Chemo. Conclusion The PFS results suggested that olaparib, talazoparib, and Vel+platinum agent+Chemo were ideal regimens for overall, TNBC, and advanced BC patients with gBRCA mutations. Whether PARPis are suitable for patients with gBRCA mutations who have received prior platinum therapy still needs to be clarified.